Distribution and statistical correlations of major, minor and trace metals in lake environments of Antarctica - MENTASTI, Edoardo; ABOLLINO, Ornella; ACETO, Maurizio; SARZANINI, Corrado (1998)
This paper reports the distribution of minor and trace metals determined in water, algae, soil and sediment collected in different lakes in Antarctica, during the Italian Expedition in the austral summer 1993/94. The determination of the total concentration of the following metals was performed: Al, Ba, Ca, Cd, Co, Cr, Cu, Fe, K, Mg, Mn, Na, Ni, Pb, Sr, Zn. These have been determined in Carezza Lake (two temporally separate samplings) in Tarn Flat Lake and in Inexpressible Island Lake. The analytical results have been discussed with reference to their different meaning for matrices such as soil and sediment. Bivariate plots obtained with the factorial analysis for principal components have been obtained and discussed for lake water samples collected in the 1993/94 campaign and the previous ones (1989-1993). In addition a t-test correlation method showed that soil samples collected around the lakes and sediments sampled at the bottom of the lakes have equal composition with a coefficient correlation of 0.988 (95% confidence level).